Atomic Absorption Spectrophotometric Determination of Potassium Content of Soil and Leaf of Camellia oleifera from the Main Producing Areas of Guangxi, China - Ye, Hang; Li, Kaixiang; Zhang, Naiyan; Jiang, Zepeng; Zeng, Wenjun; Xia, Yingying (Asian Journal of Chemistry, 2012)
The development of Camellia oleifera has a very important role on promoting integrated mountain development and the employment of rural income in Guangxi province. The concentrations of potassium in tea leaves and soils from ten major Camellia producing areas in Guangxi were measured by atomic absorption spectrophotometry. The results showed that most of the soils in central and northern Guangxi province were very deficient for potassium, so potassium deficiency is an important reason leading to low yield of Camellia forest in central and northern Guangxi.